Anti-reflux surgery in neonates and infants: analysis of indications, outcomes, and link to mortality among primary and secondary gastroesophageal reflux patients - Ibrahim A. Mostafa; Hamad A. Hader; Safwan A. Khan; Ahmed M. Hilal; Mohamed A. Gathradi; Ashraf H. M. Ibrahim (SpringerOpen, 2022)
Abstract Background The indications and benefits of anti-reflux surgery (ARS) in neonates and infants are uncertain. Prematurity, operation before 1 year of age, neurological impairment (NI), and chronic lung disease (CLD) are risk factors for surgical failure. We aim to document the indications, management, and outcomes of ARS in this age group and compare them among primary and secondary gastroesophageal reflux (GERD). Results Between January 2008 and December 2019, 24 males and 22 females had ARS; 13 (28.3%) for primary while 33 (71.7%) for secondary GERD. The mean gestational age was 34.6 weeks (range 24-41) and mean birth weight was 2000 gm (range 600-3300). The weight at time of referral ranged from 1.4 kg to 4 kg (mean 2.2 kg). There were no significant differences between the two groups regarding the previous data. The group of primary GERD presented mainly with recurrent aspiration (n = 8), recurrent apnea (n = 5), and recurrent desaturations with or shortly after feeds (n = 4). The group of secondary GERD were referred for poor sucking with failure to thrive (FTT) (n = 25), recurrent aspiration (n = 20), and gastrostomy request (n = 14). The risk factors for secondary GERD were neurologically impaired (n = 22), post-esophageal atresia (EA) repair (n = 9), hiatus hernia (n = 4), thoracic stomach (n = 2), N-type tracheoesophageal fistula (TEF, n = 4), and congenital esophageal stenosis (CES, n = 4). The operations included open Nissen's fundoplication (ONF) (n = 4) and modified open Thal's fundoplication (MOTF) (n = 42). There were 8 mortalities in the secondary group, unrelated to surgery. Morbidities after Nissen's fundoplication included wrap migration, gas bloat, and reoperation in one, laparotomy for intestinal obstruction (IO) in one. Following MOTF, there were two cases of transient recurrent GERD which improved with time and laparotomy in one for IO. Conclusions Diagnostic tests remain a challenge. Isolated TEF and CES may require fundoplication for staged management. Cases of the primary group did better with MTFO. Prematurity, CLD and age < 2 months were not significant risk factors for fundoplication failure or mortality. Neurological impairment was a risk factor for mortality.